SELF ASSESSMENT PENERAPAN TATA KELOLA PT BANK MANDIRI (PERSERO) Tbk - Faradina Inda Wardhani (Jurnal Ekonomi Integra, 2019)
Good corporate governance (GCG) is used by companies to improve the quality of earnings by taking into account the interests of stakeholders are based on the rule of law and norms. System of good corporate governance requires built and executable principles of corporate governance (GCG) in the process of managerial companies. The method used in this research is descriptive and verification method. Based on the research results, it can be concluded that the principles of good corporate governance at Bank Mandiri are measured using the dimensions of transparency, accountability, responsibility, independence and fairness in excellent criteria.